Performance investigation of a waste heat driven pressurized adsorption refrigeration cycle - Habib, K. (Institute of Physics Publishing, 2015)
This article presents performance investigation of a waste heat driven two bed pressurised adsorption refrigeration system. In this study, highly porous activated carbon (AC) of type Maxsorb III has been selected as adsorbent while n-butane, R-134a, R410a, R507a and carbon dioxide (CO2) are chosen as refrigerants. All the five refrigerants work at above atmospheric pressure. Among the five pairs studied, the best pairs will be identified which will be used to provide sufficient cooling capacity for a driving heat source temperature above 60°C. Results indicate that for a driving source temperature above 60°C, AC-R410a pair provides highest cooling capacity while AC-CO2 pairs works better when the heat source temperature falls below 60°C.